1991
DOI: 10.1002/jat.2550110603
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of organophosphorus compounds on calmodulin activity

Abstract: In vitro effects of organophosphorus compounds (OP), such as malathion (M), methyl parathion (MP) and ethyl parathion (EP), on calmodulin (CaM) activity and its active conformation were studied to understand the mechanism(s) of neurotoxicity, since CaM is known to regulate Ca2+ transport and the enzymes involved in signal transduction and nucleotide metabolism. The biological activity of CaM was assessed as a measure of phosphodiesterase (PDE) stimulation. The effect of OP compounds on the active conformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Furthermore, OP compounds inhibit calmodulin activity and its active conformation (Pala et al, 1991). Jung et al (2003) demonstrated that the N-nitroso metabolite of carbofuran, N-nitrosocarbofuran induces apoptosis in mouse brain microvascular endothelial cells, at least in part through the ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, OP compounds inhibit calmodulin activity and its active conformation (Pala et al, 1991). Jung et al (2003) demonstrated that the N-nitroso metabolite of carbofuran, N-nitrosocarbofuran induces apoptosis in mouse brain microvascular endothelial cells, at least in part through the ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore used N-phenyl-I -naphthylamine, an analogue of this probe, that lacks the sulphonate group and which is more specifically targeted to hydrophobic patches of aFGF exposed upon acidification. This molecule has also been previously used to monitor the enhanced exposure of the hydrophobic cores of proteins generated by conformational changes [33]. The results of the binding of N-phenyl-1-naphthylamine to aFGF, at different that some hydrophobic patches persist in the protein at pH 2.0.…”
Section: N-phenyl-1-naphthylamine Binding Molten Globule Interme-mentioning
confidence: 99%
“…For example, the MAL-M exposure significantly altered genes involved in the protein kinase A signaling pathway, which is essential in maintaining olfactory signal transduction, including odor-induced response (Vielma et al, 2008) and axon pathfinding in fish ORNs (Yoshida et al, 2002). In vitro studies have suggested involvement of calcium signaling in MALinduced neurotoxicity, likely via inhibiting calmodulin (CaM) activity (Pala et al, 1991). We observed a down-regulation of CAMK2A, which may also suggest an interference of calcium signaling by MAL exposure.…”
Section: Discussionmentioning
confidence: 60%